Religious Conversion in the Era of Cyber Proselytism in Indonesia: A Critical Discourse Analysis of Social Media Religious Content - Warsito, Loekisno Choiril; Ly, Le Ngoc Bich (Religió Jurnal Studi Agama-agama, 2026)
The proliferation of social media has transformed online spaces into arenas of active religious persuasion, as evidenced by conversion movements organized around hashtags such as #hijrah and #SaveMaryam. This study addresses religious conversion in the era of cyber through a Critical Discourse Analysis (CDA) of 68 purposively sampled content items drawn from Instagram, YouTube, TikTok, and WhatsApp, published between 2021 and 2025, encompassing both Islamic da’wa and Christian cyber evangelism. The analysis integrates Fairclough’s three-dimensional model, van Dijk’s socio-cognitive approach, and Wodak’s discourse-historical framework with digital religion theory and Rambo’s model of religious conversion. Four principal discursive strategies are identified: authenticity discourse; accessibility discourse; community discourse; and crisis discourse. These strategies constitute an integrated “persuasive ecology” in which each reinforces the others to address the cognitive, emotional, and social dimensions of religious persuasion simultaneously. The findings demonstrate that cyber proselytism is not traditional religious persuasion transposed into digital form but a qualitatively new discursive formation shaped by platform affordances and algorithmic logics.